TOKOH BIMA PADA LAKON DEWA RUCI SEBAGAI IDE PENCIPTAAN MOTIF BATIK WAYANG UNTUK FUNGSI HIASAN DINDING - Insyafi, Mohammad Edo; Affanti, Tiwi Bina (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2024)
The Dewa Ruci puppet play is one of the traditional wayang stories rich in values and teachings about achieving the perfection of life. This creation aims to revive moral values of virtue and nobility by reinterpreting the visuals from the Dewa Ruci story into wall decorations. The artwork creation employs Gustami's three-phase, six-step craft-making method, consisting of exploration, design, and realization phases. The resulting works serve as a medium of expression through batik painting techniques designed for premium wall decoration products. These artworks, created on marsoto canvas, exude expressive and abstract qualities, offering a fresh visual sensation, differentiation, and innovation.